Mecanismos para elaboração de uma política pública visando à erradicação da exploração sexual de crianças e adolescentes no chamado turismo sexual na cidade do Rio de Janeiro - Veras, Thaísa Restani (2008)
The main objective of this dissertation is to propose mechanism in order to elaborate a public policy to eradicate child and teenage sexual exploitation at called sex tourism in Rio de Janeiro city. So, it is reflect upon theory of the theme, considering the situation of social vulnerability that major part of the population is located. Besides, defines the meaning of public policy in order to understand how they can help in the solution of the main problem. Data was collected through personal interviews based on unstructured script, to make possible the construction of a relation between a bibliographical review and an in loco perception of sex professionals about the subject. Therefore, it was possible to achieve the final objective and to propose themes for future studies.